DIGITALISASI SISTEM MANAJEMEN MUTU ISO BERBASIS APLIKASI WEB - Purnomo Hadi Susilo; M Ghofar Rohman (Joutica, 2017)
Control and distribution of documents is a problem that often occurs in an institution/company that has implemented a Quality Management System (QMS) ISO. Solutions that can be done is to change conventional management into digital management through information technology that is able to distribute information quickly, accurately and in real time. This study aims to determine the level of use, efficiency, effectiveness, and satisfaction of users of the product to be built. The results of this study indicate that the products have been built to improve the efficiency and effectiveness of the performance of the user who serves as the perpetrators of ISO management, and can be used as a solution to get the ISO quality management is more reliable in the era of digitalization.